The Quranic Discourse on Animals and Its Relevance to Modern Zoology - Salma Kaleem; Muhammad Yaqoob (`, 2025)
This paper discusses the theological and ethical meaning of animals in the Quran, and evaluates how the animals mentioned in the scriptures correspond to the present-day zoological knowledge. There are more than 200 direct and indirect references to the animal world in the Quran, and bees, ants, camels, and whales serve not only as biological creatures: they are also represented as signs of God (ayat), exemplars, and actors in prophetic fables. Examining verses describing bees in Surah An-Nahl, ant colonies in Surah An-Naml, and an ant to consider the camel in Surah Al-Ghashiyah, the article creates scientific correlations of the subjects of the insect communication, adaptations to the desert, or marine life. The Quranic worldview involves the ethical aspect that is supported by the idea of mizan (balance), khalifah (stewardship) and divine accountability which, in their turn, promote environmental conservation, animal rights and sustainable relationship with nature. Moreover, the paper criticizes compulsory scientific harmonic and rather advocates a reflective, symbolic, and epistemologically pluralistic attitude to scriptural zoology. Although the Quran is not a scientific textbook, the moral code and theology that underlies it complements the modern-day issues of biodiversity, ecological justice, and treatment of animals as living beings. The exchange between the Quranic doctrine and the contemporary science proves the validity of Islamic thinking in the contemporary ecological and ethical discussion, a spiritually embedded but intellectually sound explanation of the interaction between people, animals, and environment. Keywords: Quran, Animals, Islamic Environmental Ethics, Zoology, Quranic Ecology, Bee Communication, Animal Rights, Scientific Parallels